Blood biomarkers associated with neurological deterioration in patients with acute penetrating artery territory infarction: A multicenter prospective observational study. Issue 2 (February 2018) - Kawano, Tomohiro; Miyashita, Kotaro; Takeuchi, Mariko; Nagakane, Yoshinari; Yamamoto, Yasumasa; Kamiyama, Kenji; Manabe, Yasuhiro; Todo, Kenichi; Metoki, Norifumi; Akaiwa, Yasuhisa; Toyoda, Kazunori; Nagatsuka, Kazuyuki
Background and purpose: Neurological deterioration in acute penetrating artery territory infarction is unpredictable and associated with unfavorable clinical outcomes. The aim of this prospective study was to clarify the cause of neurological worsening and predict clinical outcomes using blood biomarkers. Methods: Eight Japanese stroke centers participated. Blood samples were obtained within 24 h (the first sampling) and on day 7 in hospital (the second sampling) in patients with penetrating artery territory infarction, arriving within two days of stroke onset. Symptomatic worsening was defined as a minimum increase of one point on the National Institutes of Health Stroke Scale. Poor outcome was defined as a modified Rankin Scale score of ≥3 at 90 days after ictus. Results: Of the 89 patients, 25 (28%) had symptomatic worsening, and 25 (28%) had a poor outcome. Although tumor necrosis factor-alpha, high-sensitivity C-reactive protein levels were significantly increased in both groups at the second sampling, soluble lectin-like oxidized low-density lipoprotein receptor-1, CD40 ligand, and pro-adrenomedullin levels were significantly increased and ADAMTS13 activity was decreased in symptomatic worsening patients ( p  < 0.05 for all). After multivariate adjustment, a low number of CD34+ cells at the first sampling was an independent predictor of poor outcome (odds ratio, 0.20; 95% confidence interval, 0.04–0.74, p  = 0.011, per 1 cell/µl increase). Conclusions: Blood biomarkers associated with atherosclerotic processes seem to be an indication for symptomatic worsening, and the number of CD34+ cells may help to predict three-month functional outcome in patients with penetrating artery territory infarction.